2013
DOI: 10.1007/s13238-013-3032-y
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory supercomplexes: structure, function and assembly

Abstract: The mitochondrial respiratory chain consists of 5 enzyme complexes that are responsible for ATP generation. The paradigm of the electron transport chain as discrete enzymes diffused in the inner mitochondrial membrane has been replaced by the solid state supercomplex model wherein the respiratory complexes associate with each other to form supramolecular complexes. Defects in these supercomplexes, which have been shown to be functionally active and required for forming stable respiratory complexes, have been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 79 publications
0
54
0
Order By: Relevance
“…As ubiquitous energy organelles, mitochondria provide most of the adenosine triphosphate (ATP) for cells through the respiratory chain comprising several complex and supercomplex (13). NADH-ubiquinone oxidoreductase is a complex containing 44 subunits.…”
Section: A Series Of Nbp Potential Targets Resulting From Search Are mentioning
confidence: 99%
See 1 more Smart Citation
“…As ubiquitous energy organelles, mitochondria provide most of the adenosine triphosphate (ATP) for cells through the respiratory chain comprising several complex and supercomplex (13). NADH-ubiquinone oxidoreductase is a complex containing 44 subunits.…”
Section: A Series Of Nbp Potential Targets Resulting From Search Are mentioning
confidence: 99%
“…Disassociation or mutation of this complex exists within many human disorders such as Leigh syndrome (14). Of note, pathological defects of mitochondrial respiration have a close correlation with both acute neuronal trauma and chronic neurodegenerative diseases (13). Metformin, as an inhibitor of NADHubiquinone oxidoreductase, is proved to exert protective role in ischemic stroke through suppression of ROS (reactive oxygen species).…”
Section: A Series Of Nbp Potential Targets Resulting From Search Are mentioning
confidence: 99%
“…However, fewer papers reported that association of the mitochondrial respiratory chain complexes form higher supramolecular structures, which are called mitochondrial respiratory supercomplexes. These supercomplexes can take electrons from NADH to reduce oxygen (Acín-Pérez et al, 2008;Althoff et al, 2011;Vartak et al, 2013). Mitochondria exert a pivotal role in mediating cell proliferation and apoptosis (Zhang et al, 2007), and mitochondrial dysfunction is a hallmark of many genetic diseases and tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Coenzyme Q and cytochrome c have also been shown to associate with RCS (15), and recent evidence indicates that there are two distinct pools of coenzyme Q that are dedicated to reducing equivalents from NADH or reduced flavin adenine dinucleotide (16). RCS assemble to facilitate more-efficient electron transfer and to allow the utilization of different electron transport pathways and substrates during oxidative phosphorylation, to stabilize complex I and other complexes, and to limit the production of reactive oxygen species (ROS) generated from electron transport during oxidative phosphorylation (8,14,(16)(17)(18)(19). Altogether, these effects support the importance of RCS for optimal mitochondrial function.…”
mentioning
confidence: 99%